Baseline brain and behavioral factors distinguish adolescent substance initiators and non-initiators at follow-up - McQuaid, Goldie A.; Darcey, Valerie L.; Patterson, Amanda E.; Rose, Emma Jane; VanMeter, Ashley S.; Fishbein, Diana H. (Frontiers in Psychiatry, 2022)
Background Earlier substance use (SU) initiation is associated with greater risk for the development of SU disorders (SUDs), while delays in SU initiation are associated with a diminished risk for SUDs. Thus, identifying brain and behavioral factors that are markers of enhanced risk for earlier SU has major public health import. Heightened reward-sensitivity and risk-taking are two factors that confer risk for earlier SU. Materials and methods We characterized neural and behavioral factors associated with reward-sensitivity and risk-taking in substance-naïve adolescents (N = 70; 11.1–14.0 years), examining whether these factors differed as a function of subsequent SU initiation at 18- and 36-months follow-up. Adolescents completed a reward-related decision-making task while undergoing functional MRI. Measures of reward sensitivity (Behavioral Inhibition System-Behavioral Approach System; BIS-BAS), impulsive decision-making (delay discounting task), and SUD risk [Drug Use Screening Inventory, Revised (DUSI-R)] were collected. These metrics were compared for youth who did [Substance Initiators (SI); n = 27] and did not [Substance Non-initiators (SN); n = 43] initiate SU at follow-up. Results While SI and SN youth showed similar task-based risk-taking behavior, SI youth showed more variable patterns of activation in left insular cortex during high-risk selections, and left anterior cingulate cortex in response to rewarded outcomes. Groups displayed similar discounting behavior. SI participants scored higher on the DUSI-R and the BAS sub-scale. Conclusion Activation patterns in the insula and anterior cingulate cortex may serve as a biomarker for earlier SU initiation. Importantly, these brain regions are implicated in the development and experience of SUDs, suggesting differences in these regions prior to substance exposure.